Understanding Terminological Systems II: Experience with Conceptual and Formal Representation of Structure - de Keizer, N. F.; Abu-Hanna, A. (Methods of Information in Medicine, 2000)
This article describes the application of two popular conceptual and formal representation formalisms, as part of a framework for understanding terminological systems. A precise understanding of the structure of a terminological system is essential to assess existing terminological systems, to recognize patterns in various systems and to build new terminological systems. Our experience with the application of this framework to five well-known terminological systems is described.
Keywords: Terminological System; Conceptual Representation; Formalization